Combining Cognitive Behavioural Therapy and Pharmacotherapy in the Treatment of Anxiety Disorders: True Gains or False Hopes? - (:unkn) unknown (KURE ILETISIM GRUBU A S, 2009)
Objective: Anxiety disorders are common and have negative impact on the individual, the health system and the society. In practice a substantial percentage of patients remain untreated and those who are treated mostly receive either pharmacotherapy or CBT as monotherapy or in combination. This article aims at reviewing the available evidence for and against combination therapy in anxiety disorders with special emphasis on panic disorder and explores possible mechanisms of how cognitive behavioural therapy (CBT) and pharmacotherapy interact. Method: The article reviews available evidence for combination therapy in panic disorder and putative interactions between CBT and pharmacotherapy for panic disorder as well as for generalized anxiety disorder (GAD), social anxiety disorder (SAD), obsessive-compulsive disorder (OCD), and post-traumatic stress disorder (PTSD) on meta-analytic level. Results: There is no high-quality data that favours combination therapy in PTSD or combination of CBT with antipsychotics or anticonvulsants. In panic disorder, GAD, SAD and OCD combined treatment with antidepressants or benzodiazepines may result in greater effectiveness during the acute phase and post-treatment but treatment gains appear not to be durable compared to CBT monotherapy. Some evidence suggests that combination with some types of medication may actually be detrimental to long-term outcome. Effects on the neuronal fear network and memory function as well as attribution of improvement and patients' attitudes towards treatment are possible factors in understanding the complex interaction between psychotropic medication and CBT. Conclusions: Combination therapy in anxiety disorders may be clinically over-used considering the current evidence base while CBT monotherapy appears underutilized. The complex interaction between pharmacotherapy and CBT should be considered in treatment planning.
Keywords: Cognitive behavioural therapy; pharmacotherapy; anxiety disorder; PANIC DISORDER; ALPRAZOLAM DISCONTINUATION; SELECTIVE SEROTONIN; AMYGDALA RESPONSE; EXPOSURE THERAPY; MEMORY; ANTIDEPRESSANTS; METAANALYSIS; AGORAPHOBIA; MEDICATION